Non-Surgical Management of Bilateral Adrenal Abscess in Neonates: Report of Two Cases - Mandelia, Ankur; Kishore, J S; Yadav, Rajnikant; Lal, Richa (Journal of Neonatal Surgery, 2017)
Adrenal hemorrhage is not uncommon in neonates but the development of an adrenal abscess is extremely rare. Bilateral adrenal abscess is even rarer with less than ten cases documented in the medical literature. It may have a fatal outcome if inadequately treated. Here, we present two cases of neonates with history of obstructed labour and meconium aspiration who presented with bilateral adrenal abscesses. The abscesses were successfully treated using ultrasound-guided percutaneous drainage along with administration of appropriate intravenous antibiotics.